2015
DOI: 10.1002/env.2350
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of return values for ocean wave characteristics in the South China Sea using directional–seasonal extreme value analysis

Abstract: Estimation of ocean environmental return values is critical to the safety and reliability of marine and coastal structures. For ocean waves and storm severity, return values are typically estimated by extreme value analysis of time series of measured or hindcast sea state significant wave height H S . For a single location, this analysis is complicated by the serial dependence of H S in time and its non-stationarity with respect to multiple covariates, particularly direction and season. Here, we report a non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…These authors have performed a number of recent analyses similar to that reported here using maximum likelihood inference, incorporating cross‐validation to estimate optimal spline roughness penalty coefficients and an all‐encompassing bootstrap scheme to estimate uncertainties in model parameters and return values (e.g., Jonathan et al , ; Feld et al , ). In particular, we have performed a direct comparison of maximum likelihood and Bayesian inference for the South China Sea application (reported in Randell et al , ), obtaining good agreement for model parameter and return value estimates. Moreover, maximum likelihood inferences for the northern North Sea location considered here are provided in the Supporting Information accompanying this work, again showing good agreement between maximum likelihood and Bayesian inferences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors have performed a number of recent analyses similar to that reported here using maximum likelihood inference, incorporating cross‐validation to estimate optimal spline roughness penalty coefficients and an all‐encompassing bootstrap scheme to estimate uncertainties in model parameters and return values (e.g., Jonathan et al , ; Feld et al , ). In particular, we have performed a direct comparison of maximum likelihood and Bayesian inference for the South China Sea application (reported in Randell et al , ), obtaining good agreement for model parameter and return value estimates. Moreover, maximum likelihood inferences for the northern North Sea location considered here are provided in the Supporting Information accompanying this work, again showing good agreement between maximum likelihood and Bayesian inferences.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated the utility of the model in application to a directional-seasonal analysis of storm peak significant wave height at a northern North Sea location and estimation of predictive directional-seasonal return value distributions necessary for the design and reliability assessment of marine and coastal structures. These authors have performed a number of recent analyses similar to that reported here using maximum likelihood inference, incorporating cross-validation to esti-mate optimal spline roughness penalty coefficients and an all-encompassing bootstrap scheme to estimate uncertainties in model parameters and return values (e.g., Jonathan et al, 2014;Feld et al, 2015). In particular, we have performed a direct comparison of maximum likelihood and Bayesian inference for the South China Sea application (reported in Randell et al, 2015), obtaining good agreement for model parameter and return value estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating seasonal effects could be an another area of potential application though in case of the South China Sea there appears to be a direct correlation between directional and seasonal effects (Randell et al, 2015a). However it would be worthwhile to establish such a model in the spatial context to actually see the full relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, new deductive methods for data extrapolation were developed. These rely on non-stationary extreme value analysis, hereafter referred to as CEVA ("Covariate Extreme Value Analysis") and are described in ( [1], [18], [19], [20]). Briefly, CEVA performs a non-stationary directional-seasonal analysis of storm peak significant wave height using a penalized maximum likelihood approach.…”
Section: Introductionmentioning
confidence: 99%